Peran Majelis Shalawat Dhiya'ul Hadi dalam Penguatan Pemahaman Keagamaan Masyarakat Kota Tanjungbalai - Amanatin Nazwa; Indi Yusmardani; Mustofa Abdullah Nasution; Solihah Titin Sumanti; Zaini Dahlan (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
This study aims to examine the role of the Dhiya’ul Hadi Mosque Council in strengthening the religious understanding of the people of Tanjungbalai City through continuous empowerment activities and religious guidance. This study uses a qualitative method with a descriptive approach. Data diperoleh melalui observasi, wawancara, dan dokumentasi. The research information includes the head of the committee, the committee members, and the community members who participate in the Dhiya’ul Hadi Shalawat Assembly activities. The study shows that the Dhiya’ul Hadi Mosque of Blessings has been actively involved in strengthening the religious understanding of the community through various regular programs, such as reading Ratib Al-Haddad, Ratib Al-Athos, Rawi Dhiyaul Lami’, shalawat gatherings, hadrah sessions, book discussions, and the Maulid Arbain event that takes place over 40 days and 40 nights in the month of Rabiul Awal. In addition, the council provides religious guidance through sermons held after the recitation of salawat and dhikr, using materials from the books Al-Anwarul Muhammadiyah, Assyifa, Nashoih Diniyyah, Safinah, Tanqihul Qaul, and Al-Minhajus Sawi. This activity has a positive impact on improving religious understanding, strengthening spirituality, enhancing the quality of worship, fostering love for Allah Swt and the Prophet Muhammad Saw, and strengthening Islamic brotherhood within the community. Therefore, the Shalawat Dhiya’ul Hadi Council has successfully become an effective informal Islamic education institution that empowers and guides the community to strengthen their religious understanding and apply Islamic values in their daily lives.